Thermodynamic Studies of the Molecular Interactions of 2,3-Dichloro-5,6-Dicyano-Benzoquinone with meso-Tetraarylporphyrins - ZABARDASTI, ABEDIEN; MIRZAEIAN, MOHAMMAD (Asian Journal of Chemistry, 2010)
The interactions of 2,3-dichloro-5,6-dicyano-benzoquinone (DDQ) with free bases para-substituted meso-tetraphenylporphyrins (H2T(4-X)PPs; X = OCH3, CH3, H and Cl) results adducts of composition 2:1 of DDQ to H2T(4-X)PP, [(DDQ)2(H2T(4-X)PP)]. Formation constants, K, as well as other thermodynamic parameters, ΔH°, ΔS° and ΔG° of adducts were determined by UV-Vis titration method. Adducts have negative values of ΔH°, ΔS° and ΔG°. Adducts stabilities decrease in the order: H2T(4-OCH3)PP > H2T(4-CH3)PP > H2TPP > H2T(4-Cl)PP.